Pelatihan Welding Procedure Specification (WPS) untuk Meningkatkan Kompetensi Mahasiswa Menghadapi Kebutuhan Dunia Kerja - Albertus Laurensius Setyabudhi; Yuni Hardi; Amelia Rachmi Nasution; Lucky Agustin; Agustin Dwi Sumiwi; Ramdhani Yusli Arbain Sugoro; Okta Veza; Nofri Yudi Arifin (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
The competency gap between university graduates and industrial requirements remains a significant challenge in preparing job-ready human resources, particularly in the welding sector. One of the essential competencies required by industry is the ability to understand and interpret the Welding Procedure Specification (WPS) as the primary document governing welding operations in accordance with international standards. This community service program aimed to enhance students' competencies in understanding the concepts, structure, and implementation of WPS to improve their readiness for the industrial workforce. The program was organized by the Department of Logistics Engineering and the Department of Naval Architecture Engineering, Faculty of Science and Technology, Universitas Ibnu Sina, in collaboration with the Alumni Association of Institut Teknologi Sepuluh Nopember (IKA ITS), using a Participatory Training and Practice-Based Learning approach. The activities included competency needs assessment, lectures on WPS, Procedure Qualification Record (PQR), Welder Performance Qualification (WPQ), ASME Section IX and AWS D1.1 standards, industrial case studies, practical interpretation of WPS documents, interactive discussions, and program evaluation. The results demonstrated that participants significantly improved their understanding of WPS functions, the relationship between WPS and PQR, welding parameters, and the application of international standards in fabrication processes. The program also enhanced participants' awareness of industrial competency requirements while strengthening collaboration between higher education institutions and industry practitioners. The WPS training proved to be an effective approach for improving students' technical competencies, reducing the gap between academic learning and industrial practice, and supporting graduate readiness for careers in manufacturing, construction, oil and gas, and shipbuilding industries.